The Wolf's curse - Vitalis, Jessica (Greenwillow Books, an imprint of HarperCollins Publishers, 2021)
Accused of witchcraft and shunned by his fearful village, twelve-year-old carpenter's apprentice Gauge allies with another orphan to prove his innocence and capture the magical wolf hounding his every move.